2013
DOI: 10.1007/s12149-013-0763-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short-term vitamin E against radioiodine-induced early lacrimal gland damage

Abstract: According to study results, histopathological examinations revealed that vitamin E protects rat lacrimal glands against RAI-related early damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
7
0
4
Order By: Relevance
“…Upadhyaya et al (15) detected the protective effect of vitamin E against the radio-iodine-induced damage in salivary glands. Acar et al (13) proposed the anti-infl ammatory and anti-fi brotic effect of vitamin E against the damage in lacrimal glands of RAI-administered rats. In a study by Ramos et al (24) the protective effect of vitamin E in single dose radiation-applied rats was detected by measuring the volume of saliva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upadhyaya et al (15) detected the protective effect of vitamin E against the radio-iodine-induced damage in salivary glands. Acar et al (13) proposed the anti-infl ammatory and anti-fi brotic effect of vitamin E against the damage in lacrimal glands of RAI-administered rats. In a study by Ramos et al (24) the protective effect of vitamin E in single dose radiation-applied rats was detected by measuring the volume of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E, which is non-toxic, has been used in the treatment of diseases such as cataract, cancer and cardiovascular diseases (12). Recent studies have revealed that vitamin E has a radio-protective effect against lacrimal and salivary gland damage which occurs in patients receiving RAI treatment (13,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings demonstrate the importance of alerting health professionals and patients to the possibility of occurrence of these events for early diagnosis and treatment. Although there is no effective method to prevent the adverse effects of radioiodine therapy on the lacrimal system, the use of antioxidants, such as vitamin E, lycopene, and montelukast, or NIS blockers, such as perchlorate, are potential therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings demonstrate the importance of alerting health professionals and patients to the possibility of occurrence of these events for early diagnosis and treatment. Although there is no effective method to prevent the adverse effects of radioiodine therapy on the lacrimal system, the use of antioxidants, such as vitamin E, 56 lycopene, 57 and 59 are potential therapeutic options. Prospective studies with a larger sample size and longer follow-up are essential to determine the measures of association, including the relative risk of ocular and nasal adverse effects in patients treated with radioiodine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Koca et al (17) recently showed that RAI treatment causes morphological damage to rat lacrimal glands, and montelukast sodium effectively protects lacrimal glands against the damage of the treatment. Acar et al (1) described RAI-induced changes in rat lacrimal glands after oral RAI administration and the effect of vitamin E in preventing these probable changes. According to the results of the current study, histopathological examinations revealed that ML protects rat liver against radioiodine related liver damage.…”
Section: Discussionmentioning
confidence: 99%